Rhizodegradation of Pyrene by a Non-pathogenic Klebsiella pneumoniae Isolate Applied With Tagetes erecta L. and Changes in the Rhizobacterial Community - Rajkumari, Jina; Choudhury, Yashmin; Bhattacharjee, Kasturi; Pandey, Piyush (Frontiers in Microbiology, 2021)
The non-clinical Klebsiella pneumoniae variants, isolated from different environments, are now well acknowledged for their role in plant-growth promotion and biodegradation of pollutants. In the present study, a non-clinical environmental isolate K. pneumoniae AWD5 is being described for rhizoremediation of pyrene, applied through the rhizosphere of an ornamental plant, Tagetes erecta L (marigold). The non-pathogenic nature of AWD5 was established using an in vivo mouse model experiment, where AWD5 was unable to cause lung infection in tested mice. Degradation of pyrene, in the presence of succinate as co-substrate, was observed to be 87.5% by AWD5, after 21 days of incubation in minimal (Bushnell–Hass) medium in vitro conditions. Consequently, the bacterial inoculation through the rhizosphere of T. erecta L. plants resulted in 68.61% degradation of pyrene, which was significantly higher than control soil. Inoculation of AWD5 also improved plant growth and exhibited an increase in root length (14.64%), dry root weight (80.56%), shoot length (3.26%), and dry shoot weight (45.35%) after 60 days of incubation. T. erecta L., an ornamental plant, was also found to be suitable for bioremediation of pyrene. The effect of AWD5 application, and rhizoremediation process, on rhizosphere bacterial diversity and community structure has been studied using the metagenomic analysis of the 16S (V3–V4) region of rRNA. 37 bacterial phyla constituted the core microbiome, which was dominated by Proteobacteria followed by Actinobacteria, Actinobacteria, and Planctomycetes for all the treatments. AWD5 inoculation enhanced the relative abundance of Firmicutes and Acidobacteria as compared with other treatments. Genus Kaistobacter and Verrucomicrobia were found to be an abundant indigenous population in pyrene-spiked soils. Bacterial richness and diversity were analyzed using the Shannon–Wiener (H) index. A lower diversity index was observed in pyrene-spiked soils. Canonical correspondence analysis (CCA) showed a possible linkage with plant growth attributes and available nitrogen content that influences diversity and abundance of the bacterial community.